Validation of RT-qPCR test for SARS-CoV-2 in saliva specimens - Luis Miguel Sosa Ávila; Martha Lucía Díaz Galvis; Mayra Alejandra Jaimes Campos; Anyela Lozano-Parra; Laura Andrea Rodríguez Villamizar; Myriam Oróstegui Arenas; Ruth Aralí Martínez-Vega; Lina María Vera Cala; Leonelo E. Bautista (Elsevier, 2022)
Background: Saliva samples may be an easier, faster, safer, and cost-saving alternative to NPS samples, and can be self-collected by the patient. Whether SARS-CoV-2 RT-qPCR in saliva is more accurate than in nasopharyngeal swaps (NPS) is uncertain. We evaluated the accuracy of the RT-qPCR in both types of samples, assuming both approaches were imperfect. Methods: We assessed the limit of detection (LoD) of RT-qPCR in each type of sample. We collected paired NPS and saliva samples and tested them using the Berlin Protocol to detect SARS-CoV-2 envelope protein (E). We used a Bayesian latent class analysis (BLCA) to estimate the sensitivity and specificity of each test, while accounting for their conditional dependence. Results: The LoD were 10 copies/mL in saliva and 100 copies/mL in NPS. Paired samples of saliva and NPS were collected in 412 participants. Out of 68 infected cases, 14 were positive only in saliva. RT-qPCR sensitivity ranged from 82.7 % (95 % CrI: 54.8, 94.8) in NPS to 84.5 % (50.9, 96.5) in saliva. Corresponding specificities were 99.1 % (95 % CrI: 95.3, 99.8) and 98.4 %(95 % CrI: 92.8, 99.7). Conclusions: SARS-CoV-2 RT-qPCR test in saliva specimens has a similar or better accuracy than RT-qPCR test in NPS. Saliva specimens may be ideal for surveillance in general population, particularly in children, and in healthcare or other personnel in need of serial testing.